REFRAMING PENDIDIKAN DI ERA DISRUPSI DIGITAL: SEBUAH KAJIAN EPISTEMOLOGIS - Kadiwanu, Agriani Stevany; Purwoko, Budi; Susarno, Lamijan Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The shift from conventional pedagogical approaches to technology-integrated education reflects epistemological changes in the era of digital disruption. Unlike previous studies that focused on practical aspects, this study examines how digitization changes the definition of knowledge in education. Through a systematic literature review of related articles, the researchers analyzed three main points: (1) changes in learning methods, (2) learning efficiency without neglecting social and ethical values, and (3) the need to develop critical thinking to equip students to interact with digital technology. The findings show that the entire education ecosystem, including policymakers, educational institutions, teachers, and students, needs to strive for a balance between the use of digital technology and educational philosophy. Rather than offering general solutions, this study proposes a contextual framework for examining the use of technology, which should be examined epistemologically so that the resulting students are innovators rather than passive consumers of digital technology. Thus, educational goals can still be maintained amid digital disruption.